How can comparative judgement become an effective means toward providing clear formative feedback to students to improve their learning process during their product-service-system design project? - Dewit, Ivo; Rohaert, Sarah; Corradi, David (Design and Technology Education: An International Journal, 2021)
This study responds to calls to further investigate ways to make feedback more effective for students in the context of higher education. More specifically it scrutinizes the feedback practice, adapted to the exceptional reality of a partly on Campus, partly online semester–long Product-Service System (PSS) design project for first Master students of X at the University of Y. To do so, an established model of feedback (Hattie & Timperley, 2007) is used as a framework to seek answers to the research question: which types (and levels) of feedback are generated when applying Comparative Judgement (CJ) to guide the students’ and teachers’ feedback formulation? Following the model, first three types of feedback: feeding up; feeding back; and feeding forward and second, four levels of feedback are discerned: task; process; self-regulatory and self. The current study describes how first year Master students (n=72) and lecturers (n=4) apply CJ to formulate feedback. We evaluate which types and levels of feedback are formulated and received by the students, both towards and from their peers and teachers. Additionally, based on a post hoc survey and reflection paper, we list the strengths and weaknesses of CJ as a method to help students to formulate, interpret and receive feedback. Finally, we identify various opportunities to improve CJ based feedback during product development cycles and its impact on learning and self–assessment of the own project process and (intermediate) results quality, and metacognitive strategies for learning.